Nauczyciel w perspektywie czasopisma „Kościół i Szkoła” (1846-1848) - Hajkowska, Monika (Studia Edukacyjne, 2025)
The Kościół i Szkoła [Church and School] magazine published in Wielkopolska (1846-1848) was addressed to lower clergy and elementary school teachers. The periodical was to strengthen the relationship between church and school and by extension, between the members of these communities. The periodical was believed to help improve elementary education and draw the attention of especially landed gentry to it. It published texts on science and upbringing, information on important educational events and school laws, lists of school works, poems and letters from teachers. The editors also constantly encouraged teachers to send in not only their own articles but also comments and observations which were often critical to didactic and methodological issues. Thus, the periodical provided an important space for the exchange of experiences among the teachers as well. In the last year of the journal’s publication, special attention was paid to the activities of the Polish Pedagogical Society, which was established in Poznań.